Assessing College Writing: Do Students Connect with the Text? - Nalabandian, Taleen; Taraban, Roman; Pittman, Jessica C.; Maliepaard, Sage (Lesya Ukrainka Eastern European National University, 2020)
Reading-response research has shown that students respond to a text by engaging various cognitive and emotional processes. The aim of the current study was to examine students’ written reactions to an assigned reading as a way to determine (1) whether students connect with the reading and (2) the differing cognitive styles they may utilize in their reactions. The methods applied two text-analytic procedures to 238 student reactions to an ethics case study. The procedures were language style matching, which is a metric of engagement, and the categorical-dynamic index, which is a metric of analytic and experiential processing. We predicted that students who more strongly connected—or engaged—with the text would also demonstrate greater analytic thinking in their written response and, conversely, those who weakly connected with the text would express a more informal response based on experience. The data were analyzed using correlation statistics. The results showed that students whose writing more closely matched with the linguistic style of the case study were more likely to use an analytical style of writing, and students whose writing weakly matched the linguistic style of the case study were more likely to use an informal narrative style of writing. Future research should examine the extent to which language style matching and an associated analytic cognitive style are emergent skills that develop over the course of a college experience.